Pengaruh Pemberian Sari Kedelai ( Glicyne MAX ) terhadap Kelancaran Asi pada Ibu Postpartum : (Di Wilayah Kerja Puskesmas Rengel Kabupaten Tuban) - Ulfa Dwi Yuliana; Umu Qonitun (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
The problem of non-smooth breast milk production can result in mothers being unable to provide exclusive breast milk to their babies. The World Health Organization (WHO) recommends that newborn babies receive exclusive breast milk for the first 6 months of life. This research aims to determine the effect of giving soybean juice (glycine max) to postpartum mothers in the work area of ​​the Rengel Community Health Center, Tuban Regency.The research design used in this research is quantitative 'quasi experimental' using the research method 'pret test and post test without control' meaning that in this study the researcher only intervened in one group without comparing the effectiveness. with the independent variable namely soybean juice and the dependent variable is smooth breastfeeding. The population in this study were all 42 postpartum mothers in the Rengel Community Health Center area, selected using a random sampling technique according to the criteria, resulting in 16 postpartum mothers. The measuring instrument used in this research was a breast milk flow observation sheet. . This research technique involves giving 250 ml of soybean juice a day and giving it for 7 consecutive days.The results of the research showed that respondents who had problems with breast milk being less than smooth, after being given the soybean juice intervention, showed that 7 (43.8%) respondents had smooth breast milk, 9 (56.3%) had very smooth breast milk. The results of the Wilcoxon Signed Rank Tests with a significance level of α = <0.05 and the calculations were carried out using SPSS version 21 for Windows software, the Asymp value was obtained. Sig. (2-tailed) = 0.000, which means that the smaller the